2018
DOI: 10.3892/mmr.2018.9602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compound 21, a non‑peptide angiotensin II type 2 receptor agonist, on general anesthesia‑induced cerebral injury in neonatal rats

Abstract: General anesthesia has a great impact on neurodevelopment. However, the mechanisms underlying this effect and therapeutic methods to address it remain limited. The present study aimed to investigate the effects of compound (C)21, a non-peptide angiotensin II type 2 receptor agonist, on general anesthesia-induced cerebral injury in neonatal rats. Neonatal Sprague Dawley rats (postnatal day 7) were randomly divided into three groups (n=6 per group): The control, isoflurane and C21+ isoflurane (C21) group. Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A more recent study demonstrated that peripheral administration of C21 after unilateral cortical traumatic brain injury in mice elicited a significant reduction in neurologic deficits, an effect that was associated with decreased inflammation and apoptosis within the peri-contusional area of the brain (Ismael and Ishrat, 2021). Beneficial effects of AT 2 R agonism in brain injury are not restricted to traumatic brain injury, as C21 treatment lessens the neuronal apoptosis and synaptic loss induced by isoflurane anesthesia of neonatal rats (Yong et al, 2018). Collectively, these findings suggest that AT 2 R activation can be beneficial in brain injury situations in adults and developing animals and that this area bears further investigation.…”
Section: E Lungmentioning
confidence: 99%
“…A more recent study demonstrated that peripheral administration of C21 after unilateral cortical traumatic brain injury in mice elicited a significant reduction in neurologic deficits, an effect that was associated with decreased inflammation and apoptosis within the peri-contusional area of the brain (Ismael and Ishrat, 2021). Beneficial effects of AT 2 R agonism in brain injury are not restricted to traumatic brain injury, as C21 treatment lessens the neuronal apoptosis and synaptic loss induced by isoflurane anesthesia of neonatal rats (Yong et al, 2018). Collectively, these findings suggest that AT 2 R activation can be beneficial in brain injury situations in adults and developing animals and that this area bears further investigation.…”
Section: E Lungmentioning
confidence: 99%
“…(i) Gamma is not expressed in the structures of the olfactory bulb, in the part of the olfactory cortex, part of the neocortex, some structures of the thalamus, nuclei of the solitary tract, dorsal motor nuclei of the vagus, and Purkinje cells (ii) Alpha is not expressed in the hypothalamus [24] All 3 isoforms are actively expressed in the basal ganglia to which amygdala belongs [24,136,137]. Thus, PPARs in high concentration are located in the brain areas involved in the formation of anxiety, including those that are widely represented in the hippocampus and amygdala.…”
Section: Ppar Researchmentioning
confidence: 99%
“…Isoflurane is one of the most commonly used inhaled anesthetics, and has been reported to contribute to long-term memory deficits (4). Anesthesia-associated neuronal apoptosis is considered to be an important mechanism involved in the neurological impairment induced by anesthesia (5,6). Notably, exposure of the developing brain to isoflurane can cause severe damage to neurological functions, which may result in persistent learning deficits and cognitive impairment (3,7).…”
Section: Introductionmentioning
confidence: 99%